1979
DOI: 10.1093/ajcn/32.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemotaxis on the interaction of cholera vibrios with intestinal mucosa

Abstract: Earlier reports from this laboratory have shown that chemotaxis is an important mechanism that expedites the in vitro association of cholera vibrios with intestinal slices and that affects the in vivo colonization and virulence of these bacteria to a significant degree. The data reported in the present communication indicate that there appears to be a chemotatic gradient attracting cholera vibrios not only to the surface of the mucus gel, but that this gradient continues for at least a considerable distance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 5 publications
1
69
0
Order By: Relevance
“…Early work by Freter et al (6,10) proposed that the ability of nonchemotactic V. cholerae to out-compete wild-type was a result of an inability of the former to enter the intestinal crypts. It was proposed that a large percentage of wild-type V. cholerae are killed by innate immune defenses within the crypts and that the out-competition of nonchemotactic V. cholerae is a direct result of avoiding such killing.…”
Section: Ccw-biased Rotation Results In Increased Infectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Early work by Freter et al (6,10) proposed that the ability of nonchemotactic V. cholerae to out-compete wild-type was a result of an inability of the former to enter the intestinal crypts. It was proposed that a large percentage of wild-type V. cholerae are killed by innate immune defenses within the crypts and that the out-competition of nonchemotactic V. cholerae is a direct result of avoiding such killing.…”
Section: Ccw-biased Rotation Results In Increased Infectivitymentioning
confidence: 99%
“…Previous work by Freter et al (6) revealed that motility is required for the establishment of an infection. However, subsequent work by two other groups indicated that motility might in fact be dispensable for infection (7,8).…”
mentioning
confidence: 99%
“…were enumerated on LB and on selective medium (LB with mecillinam for rcsC constitutive mutants). A competitive index (CI) for each mutant was calculated as the ratio between the mutant and the wild-type strain in the output (bacteria recovered from the host after infection) divided by their ratio in the input (initial inoculum) (Beuzó n & Holden, 2001;Freter et al, 1981;Taylor et al, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of this organism in aquatic environments contributes to endemic disease, and the evolution of new pathogenic strains provides the potential for epidemic, and even pandemic, spread (Mel and Mekalanos, 1996). The relationship between V. cholerae motility and pathogenesis has been studied for many years (Fretter et al, 1981); however, a well-defined role for motility in this context still remains uncertain (Richardson, 1991;Gardel and Mekalanos, 1996). Some interesting links between the expression of virulence determinants and motility have been found recently.…”
Section: Glowing Squid Septic Trout and Aquatic Vibriosmentioning
confidence: 99%